Low-density aerogel with underwater elasticity as well as normal-pressure atmospheric drying preparation method and application thereof
By using the combination of oxidized cellulose and silica nanofibers and ethanol replacement technology in the aerogel, the problem of aerogel structural collapse under normal pressure drying conditions was solved, and a low-density and high-porosity aerogel was achieved Preparation, suitable for a variety of application fields.
Patent Information
- Application Number
- CN202411277788.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art is difficult to maintain the stability of the skeleton of the aerogel material under normal pressure drying conditions, resulting in the collapse of the low-density aerogel structure and the inability to maintain the normal pore structure, which limits its application in industrial production.
The oxidized cellulose nanofibers and silica nanofibers are used as construction units to enhance physical entanglement between the fibers by inducing ice templates, and ethanol replacement is used to reduce high surface tension to achieve aerogel during atmospheric drying atmospheric pressure. stability.
It realizes the low density and high porosity of the aerogel under normal pressure atmospheric drying conditions, reduces the volume shrinkage during the drying process, improves the mechanical properties and underwater elastic properties of the aerogel, and is suitable for thermal insulation and thermal insulation. , underwater detection and other fields.
Smart Images

Figure CN119118619A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aerogel preparation methods, and in particular relates to a low-density aerogel with underwater elasticity and a normal-pressure atmospheric drying preparation method and application thereof. Background Art
[0002] Aerogel is a nano-scale porous solid material formed by preparing gel through the sol-gel process and then using a certain drying method to replace the liquid phase in the gel with gas. Low-density aerogel is a type of aerogel material, with its extremely low density as its main feature. The lightest silica aerogel can even reach 0.16mg / cm 3 , which is only 1 / 6 of the density of air. Due to its extremely low density and developed porous structure, low-density aerogels usually have excellent thermal insulation and sound insulation properties and good mechanical properties, which makes them have broad application prospects in the fields of thermal insulation, aerospace, environmental governance, etc. In recent years, the underwater elastic properties of aerogels have received extensive attention and in-depth research, which makes aerogels show application potential in more fields.
[0003] In order to achieve good underwater elastic performance, aerogels need to have a low density to reduce the weight burden and provide buoyancy support; at the same time, they need to have a high porosity to provide sufficient space for elastic response; in addition, the pore structure and distribution need to be reasonably controlled to obtain the best mechanical properties and stability. However, excessive pursuit of low density may cause the aerogel skeleton structure to become fragile and affect its overall performance and stability. Therefore, under the premise of maintaining the high porosity and mechanical properties of aerogels, further reducing their density puts higher requirements on the preparation process of low-density aerogels.
[0004] Because the fine micro-nano pore structure of wet gel is difficult to withstand the structural collapse caused by surface tension at the liquid-gas interface under atmospheric drying conditions at normal pressure, it is impossible to maintain a normal pore structure. Therefore, low-density aerogels are usually dried by freeze drying and supercritical CO2 drying. Both methods can effectively avoid the collapse of the aerogel structure, thereby ensuring the low density and high porosity of the aerogel.
[0005] However, freeze drying requires specific equipment, ultra-low temperature cold trap <-50℃ and high vacuum environment <100Pa, and takes >48h; while supercritical CO2 drying also involves special equipment and uses liquid carbon dioxide, which is costly and inefficient, and sometimes requires the use of toxic solvents such as acetone, which is not environmentally friendly. This makes it difficult to achieve industrial production of low-density aerogels that can be prepared under laboratory conditions.
[0006] How to maintain the stability of the aerogel material skeleton during the normal pressure drying process, avoid drastic drying shrinkage, and obtain ultra-low density and ultra-high porosity aerogel products is an urgent problem to be solved in the process of promoting the industrial production of low-density aerogels. Summary of the invention
[0007] In order to solve the problem that the structure collapse is easy to occur and the normal pore structure cannot be maintained when low-density aerogel is prepared by normal pressure drying, the present invention provides a low-density aerogel with underwater elasticity and a normal pressure atmospheric drying preparation method and application thereof.
[0008] The technical solution of the present invention:
[0009] A low-density aerogel with underwater elasticity has a double-nanofiber skeleton. The double-nanofiber is oxidized cellulose nanofiber and silicon dioxide nanofiber. The mass ratio of the oxidized cellulose nanofiber to the silicon dioxide nanofiber is 2:3-4:1.
[0010] A method for preparing low-density aerogel with underwater elasticity by atmospheric drying at normal pressure comprises the following steps:
[0011] Step 1: Preparation of oxidized cellulose nanofiber dispersion:
[0012] The wood pulp is dispersed in deionized water, and an oxidation reaction is carried out by TEMPO oxidation method. During the reaction, an alkali solution is added dropwise to adjust the pH of the reaction system to 10.5. When the pH reaches 10.5, the reaction ends. The product is collected and washed to neutral to obtain oxidized cellulose. After circulating high-pressure homogenization, an oxidized cellulose nanofiber dispersion is obtained.
[0013] Step 2, preparing silicon dioxide nanofibers;
[0014] The polyvinyl alcohol aqueous solution and the silica precursor sol solution are mixed and stirred evenly to obtain a spinning solution, and the spinning solution is electrostatically spun to obtain a nanofiber membrane; the obtained nanofiber membrane is calcined at high temperature to obtain a silica nanofiber membrane; the obtained silica nanofiber membrane is sheared and dispersed at high speed to obtain silica nanofibers;
[0015] Step 3, preparing low-density aerogel;
[0016] The silica nanofibers obtained in step 2 are added to the oxidized cellulose nanofiber dispersion obtained in step 1, and ultrasonic dispersion and mixing are performed to obtain a double-fiber dispersion. The double-fiber dispersion is introduced into a mold and frozen to obtain a double-fiber frozen block. The double-fiber frozen block is placed in an ethanol solution at room temperature for solvent replacement, and the frozen block gradually melts and the double-fiber network is shaped. After the block has completed sufficient solvent replacement, it is taken out and dried under normal pressure and atmospheric environment until the block does not change in mass, thereby obtaining a low-density aerogel.
[0017] Furthermore, the wood pulp in step 1 is at least one of bleached sulfate softwood pulp, bleached sulfate hardwood pulp, bleached sulfite softwood pulp, bleached sulfite hardwood pulp, softwood mechanical pulp and hardwood mechanical pulp; in the TEMPO oxidation method, the mass ratio of wood pulp, deionized water, TEMPO reagent and sodium bromide in the oxidation reaction system is 2:100:0.025:0.25; the amount of sodium hypochlorite added is 7.85 mmol per gram calculated based on the total mass of the oxidation reaction system.
[0018] Furthermore, in step 1, the carboxyl concentration on the surface of the oxidized cellulose is 1.2-1.4 mmol / g; the cyclic high-pressure homogenization is performed 5-10 times at a pressure of 50-100 MPa; the length of the oxidized cellulose nanofibers is 1-5 μm and the diameter is 10-20 nm; the solid content of the oxidized cellulose nanofiber dispersion is 0.5-1.8 wt%.
[0019] Furthermore, in step 2, the concentration of the polyvinyl alcohol aqueous solution is 10wt%, the silica precursor sol solution is prepared by mixing tetraethyl orthosilicate, phosphoric acid and water in a mass ratio of 10.4:0.049:9 and stirring for 4 to 8 hours, the mass ratio of the polyvinyl alcohol aqueous solution to the silica precursor sol solution is 1:1, and the mixing and stirring time is 10 to 12 hours; the electrospinning is carried out at a voltage of 17 to 20kv, the spinning solution is pumped at a constant rate of 1ml / h, the distance between the spinning needle and the receiving plate is 15 to 20cm, the ambient temperature is 25±5°C, the relative humidity is 45±5%, and the electrospinning time is 6 to 8h.
[0020] Furthermore, the high temperature calcination in step 2 is carried out in an air atmosphere by heating to 800° C. at a heating rate of 5° C. / min and calcining for 2 hours; and the high speed shear dispersion is carried out by shearing at a rotation speed of 10000 to 15000 rpm for 10 minutes.
[0021] Furthermore, in step three, the mass ratio of the oxidized cellulose nanofibers to the silicon dioxide nanofibers is 2:3 to 4:1; the ultrasonic dispersion is performed at 800W for 20 to 40 minutes in an ice-water bath; the overall solid content of the dual-fiber dispersion is 1wt%; and the freezing treatment temperature is -20 to -30°C.
[0022] Furthermore, the volume concentration of the ethanol solution in step 3 is 70-100%, and the solvent replacement is carried out at room temperature for 2-12 hours, and the number of replacements is 1-2 times.
[0023] Furthermore, the drying under normal pressure in step 3 is drying at room temperature and normal pressure or drying in an oven at normal pressure below 80° C., and the drying time is 2 to 16 hours.
[0024] A low-density aerogel with underwater elasticity is used in the fields of thermal insulation, underwater detection, underwater communication, environmental management, biomedicine, flexible electronics, sensors and intelligent devices.
[0025] Beneficial effects of the present invention:
[0026] The present invention uses cellulose nanofibers and silicon dioxide nanofibers as aerogel building units, and enhances the physical entanglement between the two phase fibers through the freezing-induced ice template method, and a stronger hydrogen bond enhancement occurs between the cellulose nanofibers to strengthen the cross-linking effect to form a more stable three-dimensional porous framework structure. Based on the ethanol-ice replacement effect, the present invention replaces the high surface tension water in the wet gel with low surface tension ethanol. The ethanol evaporates faster during the normal pressure evaporation process and plays a positive role in maintaining the porous structure of the aerogel.
[0027] The stable double-fiber network structure and the low surface tension of ethanol evaporation keep the aerogel in its original form during the subsequent atmospheric drying process, effectively reducing the volume shrinkage during the drying process. The volume shrinkage of the aerogel before and after drying in the present invention is 8.37±1.62%, which is very close to that of the freeze-drying method; the density is only 10.86±0.32mg·cm -3 ; Porosity>99.35%, thermal conductivity 25.62mW·mK -1 , which is similar to the thermal conductivity of air, and can be used in thermal insulation fields such as construction, transportation, aerospace, shipbuilding and thermal insulation packaging materials.
[0028] The present invention adopts two kinds of nanofibers with high aspect ratio, and utilizes the spatial physical entanglement and the strong hydrogen bond interaction of cellulose to effectively improve the skeleton strength, showing excellent mechanical properties; the stable double nanofiber skeleton gives the aerogel extremely high compressive strength, reaching 117.65kPa when the air impact compression strain is 80%, and reaching a maximum compression strain of 13.26kPa when the compression strain is 80% in water. Since the aerogel prepared by the present invention has high porosity and low density characteristics, it shows excellent underwater elastic properties and shape memory properties. After the aerogel is placed in underwater compression, it can fully rebound and quickly return to its original shape. This makes it have broad application prospects in the fields of underwater detection, underwater communication, environmental governance, biomedicine, flexible electronics, sensors and intelligent devices.
[0029] The present invention adopts a simple process to prepare isotropic low-density high-porosity nanofiber aerogel. The preparation process does not require additional cross-linking agents, no toxic pollutants are discharged, and ethanol can be recycled and reused as a green solvent, which is green and environmentally friendly. In the present invention, atmospheric drying at normal pressure does not require specific harsh conditions and equipment, and the entire process including replacement and room temperature drying can be shortened to 16 hours, which can greatly shorten the preparation cycle, reduce production costs and energy consumption, and has scalability, thereby improving the large-scale productivity of low-density aerogels. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The macroscopic photograph and scanning electron microscope image of the low-density aerogel CNF / SiO2-1 of Example 1;
[0031] Figure 2 The compressive stress-strain curves of the low-density aerogel CNF / SiO2-1 under different compressive strains of Example 1;
[0032] Figure 3 The macroscopic photograph and scanning electron microscope image of the low-density aerogel CNF / SiO2-2 of Example 2;
[0033] Figure 4 The compressive stress-strain curves of the low-density aerogel CNF / SiO2-2 under different compressive strains of Example 2;
[0034] Figure 5 The macroscopic photograph and scanning electron microscope image of the low-density aerogel CNF / SiO2-3 of Example 3;
[0035] Figure 6 The compressive stress-strain curves of the low-density aerogel CNF / SiO2-3 under different compressive strains of Example 3;
[0036] Figure 7 The macroscopic photograph and scanning electron microscope image of the pure cellulose nanofiber aerogel CNF / SiO2-0 of Comparative Example 1;
[0037] Figure 8 It is a compressive stress-strain curve diagram of pure cellulose nanofiber aerogel CNF / SSiO2-0 under different compressive strains of comparative example 1;
[0038] Fig. 9 This is a physical display diagram of the low-density aerogel of Example 1 being compressed and recovered in water;
[0039] Fig.10 This is a physical display diagram of the low-density aerogel of Example 1 being compressed and recovered in liquid nitrogen;
[0040] Fig.11This is a physical demonstration of the low-density aerogel of Example 1 quickly achieving shape memory in water. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is further described below in conjunction with the embodiments, but it is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention shall be included in the protection scope of the present invention. The process equipment or devices not specifically noted in the following embodiments are all conventional equipment or devices in the art. If not specifically specified, the raw materials used in the embodiments of the present invention can be obtained commercially; if not specifically specified, the technical means used in the embodiments of the present invention are all conventional means well known to those skilled in the art.
[0042] Example 1
[0043] This embodiment provides a low-density aerogel with underwater elasticity and a preparation method thereof.
[0044] The preparation method of the low-density aerogel in this embodiment comprises the following steps:
[0045] Step 1: Preparation of oxidized cellulose nanofiber dispersion:
[0046] 2g of softwood bleached pulp was dispersed in 100g of deionized water, and the TEMPO oxidation method was used for oxidation reaction. In contrast, 0.025g of TEMPO reagent (2,2,6,6-tetramethyl-1-piperidinyl oxide) and 0.25g of sodium bromide (NaBr) were added to the wood pulp dispersion system. 7.85mmol of sodium hypochlorite was added as an oxidant per gram calculated based on the total mass of the oxidation reaction system to start the oxidation reaction. During the entire reaction process, the pH of the reaction system was adjusted to 10.5 by dropping 0.5M NaOH solution. When the pH reached 10.5, the reaction was terminated and ethanol was added to terminate the reaction. The reaction conditions and reaction time need to be controlled to avoid excessive oxidation affecting the length of cellulose nanofibers.
[0047] The product was collected and washed several times with deionized water until it was neutral to obtain oxidized cellulose with a length of 1 to 5 μm and a diameter of 10 to 20 nm. The product was then circulated and homogenized using a high-pressure homogenizer. After homogenization five times at a pressure of 100 MPa, an oxidized cellulose nanofiber dispersion with a solid content of 1.8 wt% was obtained. The dispersion was refrigerated at 4°C before use.
[0048] In this example, bleached softwood pulp was used as raw material, and the hydroxyl groups on the cellulose molecular chain were converted into carboxyl groups by the TEMPO oxidation method. The carboxyl concentration on the surface of the obtained oxidized cellulose was 1.4 mmol / g.
[0049] Step 2, preparing silicon dioxide nanofibers;
[0050] 2g of polyvinyl alcohol (PVA, 1788) and 18g of water were stirred at 85°C for 2h to obtain a 10wt% PVA aqueous solution; tetraethyl orthosilicate TEOS, phosphoric acid and water were mixed in a mass ratio of 10.4:0.049:9, and stirred at room temperature for 8h to obtain a silica precursor sol solution; the silica precursor sol solution was slowly added to the 10wt% PVA aqueous solution in a mass ratio of 1:1, and stirred for 4h until completely dissolved to obtain a uniform spinning solution.
[0051] The spinning solution was loaded into a 5 ml syringe and pumped at a constant rate of 1 ml / h under 17 kV electrospinning high voltage. The distance between the spinning needle and the receiving electrode was 15 cm, the ambient temperature was 25±5°C, the relative humidity was 45±5%, and the PVA / TEOS electrospun nanofiber membrane was obtained after electrospinning for 6 hours.
[0052] The obtained PVA / TEOS electrospun nanofiber membrane was first placed in an oven for drying to completely remove surface moisture, and then placed in a muffle furnace, heated to 800°C at a heating rate of 5°C / min in an air atmosphere, and calcined for 2h to fully remove the organic components to obtain a silica nanofiber membrane.
[0053] The obtained silica nanofiber membrane was cut into small pieces and added into 80 ml of water. The membrane was rapidly sheared at a high speed of 15,000 rpm for 10 minutes using an XHF-DY high-speed disperser to fully shear the silica nanofibers and break up the fiber membrane into a uniformly dispersed single fiber dispersion. The dispersion was then filtered through a Buchner funnel and dried at 60°C until absolutely dry for later use.
[0054] Step 3, preparing low-density aerogel;
[0055] Deionized water was added to the oxidized cellulose nanofiber dispersion obtained in step 1 to dilute the solid content to 0.8wt%, and then 25% of the mass of cellulose nanofibers obtained in step 2 of the silica nanofibers were added to the dispersion, that is, the mass ratio of cellulose nanofibers to silica nanofibers was 4:1. Under ice-water bath conditions, 800w ultrasonic treatment was performed for 30min to fully disperse and mix the two fibers to obtain a double fiber dispersion with a total solid content of 1wt%. The obtained double fiber dispersion was introduced into an open silicone mold, and then placed in a refrigerator at -20°C for 3h to form a double fiber frozen block.
[0056] This embodiment uses an ice template to induce the self-assembly of two types of fibers to form a porous structure. The cellulose nanofibers and the silica nanofibers are strongly physically entangled and interlocked during the self-assembly process to form a stable skeleton structure.
[0057] After demolding the double-fiber frozen block, it is directly immersed in an ethanol solution with a volume concentration of 95% for ethanol replacement. The ice in the frozen block will undergo a strong melting replacement reaction with ethanol. In this process, ethanol will gradually penetrate into the frozen double-nanofiber network. Ethanol will gradually and completely replace the ice. This process will also break the original cellulose-water interaction. The melted cellulose nanofibers will further self-assemble under the action of surface hydroxyls to form a more stable network structure, thereby realizing ethanol-induced hydrogen bond fixation.
[0058] The ethanol replacement time of the present embodiment is 2h, and the frozen block gradually melts and makes the double fiber network shaped, and the block is taken out after completing sufficient solvent replacement, and dried under normal pressure atmosphere. Since ethanol has a lower surface tension than water, it shows a lower capillary force during normal pressure atmosphere drying, weakening the structural collapse problem caused by high surface tension, so that the strong skeleton remains dimensionally stable during the whole drying process. Drying to the block without mass change, that is, obtaining a low-density aerogel dried at normal pressure atmosphere, denoted as CNF / SiO2-1.
[0059] Example 2
[0060] This embodiment provides a low-density aerogel with underwater elasticity and a preparation method thereof.
[0061] The preparation method of the low-density aerogel in this embodiment comprises the following steps:
[0062] Step 1: Preparation of oxidized cellulose nanofiber dispersion:
[0063] 2 g of bleached softwood pulp was dispersed in 100 g of deionized water, and an oxidation reaction was carried out by TEMPO oxidation method. In turn, 0.025 g of TEMPO reagent (2,2,6,6-tetramethyl-1-piperidinyl oxide) and 0.25 g of sodium bromide (NaBr) were added to the wood pulp dispersion system, and 7.85 mmol of sodium hypochlorite was added as an oxidant per gram calculated based on the total mass of the oxidation reaction system to start the oxidation reaction. During the entire reaction process, the pH of the reaction system was adjusted to 10.5 by dropwise addition of 0.5 M NaOH solution. When the pH reached a constant value of 10.5, the reaction was terminated, and ethanol was added to terminate the reaction. The product was collected and washed with deionized water for multiple times until neutral, and oxidized cellulose with a length of 1 to 5 μm and a diameter of 10 to 20 nm was obtained. Subsequently, a high-pressure homogenizer was used for cyclic homogenization. After 10 times of homogenization at a pressure of 50 MPa, an oxidized cellulose nanofiber dispersion with a solid content of 1.8 wt% was obtained, which was stored in a refrigerated environment at 4°C before use.
[0064] In this example, bleached softwood pulp was used as raw material, and the hydroxyl groups on the cellulose molecular chain were converted into carboxyl groups by the TEMPO oxidation method. The carboxyl concentration on the surface of the obtained oxidized cellulose was 1.4 mmol / g.
[0065] Step 2, preparing silicon dioxide nanofibers;
[0066] 2g of polyvinyl alcohol (PVA, 1788) and 18g of water were stirred at 85°C for 2h to obtain a 10wt% PVA aqueous solution; tetraethyl orthosilicate TEOS, phosphoric acid and water were mixed in a mass ratio of 10.4:0.049:9, and stirred at room temperature for 8h to obtain a silica precursor sol solution; the silica precursor sol solution was slowly added to the 10wt% PVA aqueous solution in a mass ratio of 1:1, and stirred for 4h until completely dissolved to obtain a uniform spinning solution.
[0067] The spinning solution was loaded into a 5 ml syringe and pumped at a constant rate of 1 ml / h under 17 kV electrospinning high voltage. The distance between the spinning needle and the receiving electrode was 15 cm, the ambient temperature was 25±5°C, the relative humidity was 45±5%, and the PVA / TEOS electrospun nanofiber membrane was obtained after electrospinning for 6 hours.
[0068] The obtained PVA / TEOS electrospun nanofiber membrane was first placed in an oven for drying to completely remove surface moisture, and then placed in a muffle furnace, heated to 800°C at a heating rate of 5°C / min in an air atmosphere, and calcined for 2h to fully remove the organic components to obtain a silica nanofiber membrane.
[0069] The obtained silica nanofiber membrane was cut into small pieces and added into 80 ml of water. The membrane was rapidly sheared at a high speed of 10,000 rpm for 10 minutes using an XHF-DY high-speed disperser to fully shear the silica nanofibers and break up the fiber membrane into a uniformly dispersed single fiber dispersion. The dispersion was then filtered through a Buchner funnel and dried at 60°C until absolutely dry for later use.
[0070] Step 3, preparing low-density aerogel;
[0071] Deionized water was added to the oxidized cellulose nanofiber dispersion obtained in step 1 to dilute the solid content to 0.6wt%, and the silica nanofibers obtained in step 2 were added to the dispersion at a mass ratio of cellulose nanofibers to silica nanofibers of 3:2. Under ice-water bath conditions, ultrasonic treatment was performed at 800w for 20min to fully disperse and mix the two fibers to obtain a double fiber dispersion with a total solid content of 1wt%. The obtained double fiber dispersion was introduced into an open silicone mold, and then placed in a refrigerator at -20°C for 3h to form a double fiber frozen block.
[0072] After demolding the double-fiber frozen block, it is directly immersed in an ethanol solution with a volume concentration of 90% for ethanol replacement for 2 hours. The frozen block gradually melts and the double-fiber network is shaped. After the block has completed sufficient solvent replacement, it is taken out and dried under normal pressure and atmosphere until the mass of the block does not change. A low-density aerogel dried under normal pressure and atmosphere is obtained, which is recorded as CNF / SiO2-2.
[0073] Example 3
[0074] This embodiment provides a low-density aerogel with underwater elasticity and a preparation method thereof.
[0075] The preparation method of the low-density aerogel in this embodiment comprises the following steps:
[0076] Step 1: Preparation of oxidized cellulose nanofiber dispersion:
[0077] 2 g of bleached softwood pulp was dispersed in 100 g of deionized water, and an oxidation reaction was carried out by TEMPO oxidation method. In turn, 0.025 g of TEMPO reagent (2,2,6,6-tetramethyl-1-piperidinyl oxide) and 0.25 g of sodium bromide (NaBr) were added to the wood pulp dispersion system. 7.85 mmol of sodium hypochlorite was added as an oxidant per gram calculated based on the total mass of the oxidation reaction system to start the oxidation reaction. During the entire reaction process, the pH of the reaction system was adjusted to 10.5 by dropwise addition of 0.5 M NaOH solution. The reaction was terminated when the pH reached a constant value of 10.5. Ethanol was added to terminate the reaction. The product was collected and washed with deionized water for multiple times until neutral to obtain oxidized cellulose with a length of 1 to 5 μm and a diameter of 10 to 20 nm. Subsequently, a high-pressure homogenizer was used for cyclic homogenization. After homogenization at a pressure of 100 MPa for 5 times, an oxidized cellulose nanofiber dispersion with a solid content of 1.8 wt% was obtained, which was stored in a refrigerated environment at 4°C before use.
[0078] In this example, bleached softwood pulp was used as raw material, and the hydroxyl groups on the cellulose molecular chain were converted into carboxyl groups by the TEMPO oxidation method. The carboxyl concentration on the surface of the obtained oxidized cellulose was 1.4 mmol / g.
[0079] Step 2, preparing silicon dioxide nanofibers;
[0080] 2g of polyvinyl alcohol (PVA, 1788) and 18g of water were stirred at 85°C for 2h to obtain a 10wt% PVA aqueous solution; tetraethyl orthosilicate TEOS, phosphoric acid and water were mixed in a mass ratio of 10.4:0.049:9, and stirred at room temperature for 8h to obtain a silica precursor sol solution; the silica precursor sol solution was slowly added to the 10wt% PVA aqueous solution in a mass ratio of 1:1, and stirred for 4h until completely dissolved to obtain a uniform spinning solution.
[0081] The spinning solution was loaded into a 5 ml syringe and pumped at a constant rate of 1 ml / h under 17 kV electrospinning high voltage. The distance between the spinning needle and the receiving electrode was 20 cm, the ambient temperature was 25±5°C, the relative humidity was 45±5%, and the PVA / TEOS electrospun nanofiber membrane was obtained after electrospinning for 6 hours.
[0082] The obtained PVA / TEOS electrospun nanofiber membrane was first placed in an oven for drying to completely remove surface moisture, and then placed in a muffle furnace, heated to 800°C at a heating rate of 5°C / min in an air atmosphere, and calcined for 2h to fully remove the organic components to obtain a silica nanofiber membrane.
[0083] The obtained silica nanofiber membrane was cut into small pieces and added into 80 ml of water. The membrane was rapidly sheared at a high speed of 15,000 rpm for 10 minutes using an XHF-DY high-speed disperser to fully shear the silica nanofibers and break up the fiber membrane into a uniformly dispersed single fiber dispersion. The dispersion was then filtered through a Buchner funnel and dried at 60°C until absolutely dry for later use.
[0084] Step 3, preparing low-density aerogel;
[0085] Deionized water was added to the oxidized cellulose nanofiber dispersion obtained in step 1 to dilute the solid content to 0.4wt%, and the silica nanofibers obtained in step 2 were added to the dispersion at a mass ratio of cellulose nanofibers to silica nanofibers of 2:3. Under ice-water bath conditions, 800w ultrasonic treatment was performed for 40min to fully disperse and mix the two fibers to obtain a double fiber dispersion with a total solid content of 1wt%. The obtained double fiber dispersion was introduced into an open silicone mold, and then placed in a refrigerator at -20°C for 3h to form a double fiber frozen block.
[0086] After demolding the double-fiber frozen block, it is directly immersed in an ethanol solution with a volume concentration of 95% for ethanol replacement for 2 hours. The frozen block gradually melts and the double-fiber network is shaped. After the block has completed sufficient solvent replacement, it is taken out and dried under normal pressure and atmosphere until the mass of the block does not change. A low-density aerogel dried under normal pressure and atmosphere is obtained, which is recorded as CNF / SiO2-3.
[0087] Comparative Example 1
[0088] This comparative example provides an aerogel containing only oxidized cellulose nanofibers and a preparation method thereof.
[0089] The preparation method of the aerogel in this comparative example comprises the following steps:
[0090] Step 1: Preparation of oxidized cellulose nanofiber dispersion:
[0091] 2 g of bleached softwood pulp was dispersed in 100 g of deionized water, and an oxidation reaction was carried out by TEMPO oxidation method. In turn, 0.025 g of TEMPO reagent (2,2,6,6-tetramethyl-1-piperidinyl oxide) and 0.25 g of sodium bromide (NaBr) were added to the wood pulp dispersion system. 7.85 mmol of sodium hypochlorite was added as an oxidant per gram calculated based on the total mass of the oxidation reaction system to start the oxidation reaction. During the entire reaction process, the pH of the reaction system was adjusted to 10.5 by dropwise addition of 0.5 M NaOH solution. The reaction was terminated when the pH reached a constant value of 10.5. Ethanol was added to terminate the reaction. The product was collected and washed with deionized water for multiple times until neutral to obtain oxidized cellulose with a length of 1 to 5 μm and a diameter of 10 to 20 nm. Subsequently, a high-pressure homogenizer was used for cyclic homogenization. After homogenization at a pressure of 100 MPa for 5 times, an oxidized cellulose nanofiber dispersion with a solid content of 1.8 wt% was obtained, which was stored in a refrigerated environment at 4°C before use.
[0092] In this example, bleached softwood pulp was used as raw material, and the hydroxyl groups on the cellulose molecular chain were converted into carboxyl groups by the TEMPO oxidation method. The carboxyl concentration on the surface of the obtained oxidized cellulose was 1.4 mmol / g.
[0093] Step 2, preparing aerogel;
[0094] Deionized water was added to the oxidized cellulose nanofiber dispersion obtained in step 1 to dilute the solid content to 1.0 wt %, and the oxidized cellulose nanofiber dispersion was introduced into an open silicone mold, which was then placed in a refrigerator at -20°C for 3 hours and then formed into a frozen block.
[0095] After demolding, the frozen block is directly immersed in an ethanol solution with a volume concentration of 95% for ethanol replacement for 2 hours. The frozen block gradually melts and the network is shaped. After the block has completed sufficient solvent replacement, it is taken out and dried under normal pressure and atmosphere until the mass of the block does not change. This is to obtain aerogel dried under normal pressure and atmosphere, which is recorded as CNF / SiO2-0.
[0096] The compression modulus, volume shrinkage rate and density of the aerogels prepared in Examples 1 to 3 and Comparative Example 1 in air and water were tested. The results are shown in Table 1.
[0097] Table 1
[0098]
[0099]
[0100] The macroscopic photographs and scanning electron microscope images of the aerogels prepared in Examples 1 to 3 and Comparative Example 1 are compared. Figure 1 , Figure 3 , Figure 5 and Figure 7 As shown, the macroscopic volume shrinkage of the aerogels prepared in Examples 1 to 3 is significantly reduced compared with the pure cellulose aerogel dried at atmospheric pressure in Comparative Column 1, showing regular blocks, and there is no significant collapse and deformation of the surface and structure. In addition, the microstructures all show the characteristics of typical open-cell foams, the wall thickness becomes thicker with the increase of the amount of silica nano added, and a large number of silica nanofibers are firmly embedded in the wall layer, playing a role in structural reinforcement of the skeleton support. The comparison shows that the present invention uses two high aspect ratio nanofibers, and utilizes spatial physical entanglement and strong hydrogen bond interaction of cellulose to effectively improve the skeleton strength, forming a more stable three-dimensional porous framework structure, and always maintains the original form during atmospheric drying at atmospheric pressure, effectively reducing the volume shrinkage during the drying process, and solving the problem of structural collapse caused by high surface tension when low-density aerogels are dried at atmospheric pressure.
[0101] The compressive stress-strain of the aerogels prepared in Examples 1 to 3 and Comparative Example 1 under different compressive strains was investigated. The results are as follows: Figure 2 , Figure 4 , Figure 6 and Figure 8 As shown, by comparison, it can be seen that the compression stress-strain curve is smooth and uniform, indicating that the aerogel is uniformly compressed without structural collapse, and the aerogels prepared in Examples 1 to 3 also have certain compression rebound properties. However, due to the obvious volume shrinkage in the drying process, the comparative example 1 is smaller in volume but harder, so its maximum compression stress is relatively larger, and its rebound resilience is the worst.
[0102] The low-density aerogel prepared in Example 1 was placed in water and liquid nitrogen respectively, and a certain pressure was applied vertically to examine the underwater elastic properties of the aerogel. Fig. 9 This is a physical display of the low-density aerogel of Example 1 being compressed and recovered in water; it can be seen from the picture that during the compression process, water is squeezed out of the aerogel, and the flexible wall layer of the aerogel can be bent and folded to absorb stress deformation better, and the compressed aerogel shows lateral contraction rather than expansion, indicating that it has the characteristics of a negative Poisson's ratio. After the external force is removed, the water squeezed out of the aerogel will be quickly absorbed into the aerogel to fill the pores, so that the aerogel quickly expands and recovers to its original shape, and almost 100% volume recovery can be achieved.
[0103] Fig.10This is a physical display diagram of the low-density aerogel of Example 1 being compressed and recovered in liquid nitrogen. The picture shows that, unlike the traditional polymer aerogel that becomes brittle at low temperatures, the flexible aerogel still maintains good flexibility even at extremely low temperatures. After being immersed in extremely low-temperature liquid nitrogen, the aerogel can still be compressed to maintain its structure, and can still rebound to its original shape very quickly and fully after the external force is removed.
[0104] The low-density aerogel prepared in Example 1 was compressed in air, folded in half twice, and immersed in water to examine its underwater shape memory properties. Fig.11 This is a physical demonstration of the low-density aerogel of Example 1 quickly achieving shape memory in water. It can be seen from the picture that after the aerogel is immersed in water, it quickly completes shape recovery within 1.4 seconds, showing excellent underwater shape memory properties.
Claims
1. A low-density aerogel with underwater elasticity, characterized in that: The invention has a double nanofiber skeleton, wherein the double nanofibers are oxidized cellulose nanofibers and silicon dioxide nanofibers, and the mass ratio of the oxidized cellulose nanofibers to the silicon dioxide nanofibers is 2:3-4:
1.
2. A method for preparing a low-density aerogel having underwater elasticity by atmospheric drying at normal pressure as claimed in claim 1, characterized in that: The steps include: Step 1: Preparation of oxidized cellulose nanofiber dispersion: The wood pulp is dispersed in deionized water, and an oxidation reaction is carried out by TEMPO oxidation method. During the reaction, an alkali solution is added dropwise to adjust the pH of the reaction system to 10.
5. When the pH reaches 10.5, the reaction ends. The product is collected and washed to neutral to obtain oxidized cellulose. After circulating high-pressure homogenization, an oxidized cellulose nanofiber dispersion is obtained. Step 2, preparing silicon dioxide nanofibers; The polyvinyl alcohol aqueous solution and the silica precursor sol solution are mixed and stirred evenly to obtain a spinning solution, and the spinning solution is electrostatically spun to obtain a nanofiber membrane; the obtained nanofiber membrane is calcined at high temperature to obtain a silica nanofiber membrane; the obtained silica nanofiber membrane is sheared and dispersed at high speed to obtain silica nanofibers; Step 3, preparing low-density aerogel; The silica nanofibers obtained in step 2 are added to the oxidized cellulose nanofiber dispersion obtained in step 1, and ultrasonic dispersion and mixing are performed to obtain a double-fiber dispersion. The double-fiber dispersion is introduced into a mold and frozen to obtain a double-fiber frozen block. The double-fiber frozen block is placed in an ethanol solution at room temperature for solvent replacement, and the frozen block gradually melts and the double-fiber network is shaped. After the block has completed sufficient solvent replacement, it is taken out and dried under normal pressure and atmospheric environment until the block does not change in mass, thereby obtaining a low-density aerogel.
3. The method for preparing low-density aerogel with underwater elasticity by atmospheric drying at normal pressure according to claim 2, characterized in that: In step 1, the wood pulp is at least one of bleached sulfate softwood pulp, bleached sulfate hardwood pulp, bleached sulfite softwood pulp, bleached sulfite hardwood pulp, softwood mechanical pulp and hardwood mechanical pulp; in the TEMPO oxidation method, the mass ratio of wood pulp, deionized water, TEMPO reagent and sodium bromide in the oxidation reaction system is 2:100:0.025:0.25; the amount of sodium hypochlorite added is 7.85 mmol per gram calculated based on the total mass of the oxidation reaction system.
4. The method for preparing low-density aerogel with underwater elasticity by atmospheric drying at normal pressure according to claim 2 or 3, characterized in that: In step 1, the carboxyl concentration on the surface of the oxidized cellulose is 1.2-1.4 mmol / g; the cyclic high-pressure homogenization is performed at a pressure of 50-100 MPa for 5-10 times; the length of the oxidized cellulose nanofibers is 1-5 μm and the diameter is 10-20 nm; the solid content of the oxidized cellulose nanofiber dispersion is 0.5-1.8 wt%.
5. The method for preparing low-density aerogel with underwater elasticity by atmospheric drying at normal pressure according to claim 4, characterized in that: In step 2, the concentration of the polyvinyl alcohol aqueous solution is 10wt%, the silica precursor sol solution is prepared by mixing tetraethyl orthosilicate, phosphoric acid and water in a mass ratio of 10.4:0.049:9 and stirring for 4 to 8 hours, the mass ratio of the polyvinyl alcohol aqueous solution to the silica precursor sol solution is 1:1, and the mixing and stirring time is 10 to 12 hours; the electrospinning is carried out at a voltage of 17 to 20kv, the spinning solution is pumped at a constant rate of 1ml / h, the distance between the spinning needle and the receiving plate is 15 to 20cm, the ambient temperature is 25±5°C, the relative humidity is 45±5%, and the electrospinning time is 6 to 8h.
6. The method for preparing low-density aerogel with underwater elasticity by atmospheric drying at normal pressure according to claim 5, characterized in that: In step 2, the high temperature calcination is carried out in an air atmosphere by heating to 800° C. at a heating rate of 5° C. / min and calcining for 2 hours; the high speed shear dispersion is carried out by shearing at a rotation speed of 10,000 to 15,000 rpm for 10 minutes.
7. The method for preparing low-density aerogel with underwater elasticity by atmospheric drying at normal pressure according to claim 6, characterized in that: Step 3: The mass ratio of the oxidized cellulose nanofibers to the silicon dioxide nanofibers is 2:3 to 4:1; the ultrasonic dispersion is carried out under ice-water bath conditions at 800W for 20 to 40 minutes; the overall solid content of the dual-fiber dispersion is 1wt%; and the freezing treatment temperature is -20 to -30°C.
8. The method for preparing low-density aerogel with underwater elasticity by atmospheric drying at normal pressure according to claim 7, characterized in that: In step 3, the volume concentration of the ethanol solution is 70-100%, and the solvent replacement is carried out at room temperature for 2-12 hours, and the number of replacements is 1-2 times.
9. The method for preparing low-density aerogel with underwater elasticity by atmospheric drying at normal pressure according to claim 8, characterized in that: The drying under normal pressure in step 3 is drying under normal pressure at room temperature or drying in an oven at normal pressure below 80° C., and the drying time is 2 to 16 hours.
10. An application of the low-density aerogel with underwater elasticity as claimed in claim 1 in the fields of thermal insulation, underwater detection, underwater communication, environmental management, biomedicine, flexible electronics, sensors and intelligent devices.
Citation Information
Cited By
Lightweight heat-insulating cellulose nanofiber aerogel and preparation method thereof
CN119842113A
